2021
DOI: 10.3389/fnsyn.2021.695964
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of GluN1 at Ventral Hippocampal Synapses in the Infralimbic Cortex

Abstract: Although the infralimbic cortex (IL) is not thought to play a role in fear acquisition, recent experiments found evidence that synaptic plasticity is occurring at ventral hippocampal (vHPC) synapses in IL during auditory fear acquisition as measured by changes in the N-methyl-D-aspartate (NMDA) receptor-mediated currents in male rats. These electrophysiological data suggest that fear conditioning changes the expression of NMDA receptors on vHPC-to-IL synapses. To further evaluate the plasticity of NMDA recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…All behavioral and molecular data were analyzed with Graphpad Prism (version 9.1.0, San Diego, California). Samples sizes were based on previous studies that observed differences in similar behavior or molecular analysis (Cruz et al, 2015 ; Criado-Marrero et al, 2017 ; Castillo-Ocampo et al, 2021 ). Animals were not excluded from the data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…All behavioral and molecular data were analyzed with Graphpad Prism (version 9.1.0, San Diego, California). Samples sizes were based on previous studies that observed differences in similar behavior or molecular analysis (Cruz et al, 2015 ; Criado-Marrero et al, 2017 ; Castillo-Ocampo et al, 2021 ). Animals were not excluded from the data analysis.…”
Section: Methodsmentioning
confidence: 99%